Pengaruh Perputaran Modal Kerja, Likuiditas, Leverage, dan Pertumbuhan Penjualan terhadap Profitabilitas dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Annisa rizky ramadhani siregar; Listiorini; Mhd Karya Satya Azhar (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to determine the influence of Working Capital Turnover, Liquidity, Leverage and Sales Growth, on Profitability with Company Size as a moderation variable in the Company Food & Beverages listed on the Indonesia Stock Exchange in 2018-2023. This type of research is quantitative research that is associative. The population used in this study is Food & Beverages listed on the Indonesia Stock Exchange in 2018-2023. Sampling techniques using the Purposive Sampling With a sample of 28 companies during the observation year for 6 consecutive years, so that the total sample is 168. The analysis method of this study uses Moderated Regression Analysis (MRA). The results of the study show that the turnover of working capital, liquidity, Leverage has a significant effect on profitability, sales growth has a non-significant effect on profitability, and the size of the company is able to moderate the relationship between working capital turnover, liquidity, Leverage On profitability, company size does not moderate the relationship between sales growth and profitability